Autologous Fat Grafting in the Treatment of Cleft Lip Volume Asymmetry. (June 2018) - Koonce, Stephanie L.; Grant, David G.; Cook, Jonathan; Stelnicki, Eric J.
Abstract : Background: The goal of cleft lip repair is a symmetrical balanced lip with minimal scar. Fat grafting is an established procedure in cosmetic and reconstructive surgery for restoration or correction of contour deformity, volume loss, and improved tissue characteristics. In this study, we evaluated the use of fat grafting in correction of cleft lip volume asymmetry. Methods: We performed a retrospective analysis of our series of patients who underwent fat grafting using the Coleman technique for cleft lip volume asymmetry. Sex, age at primary repair, age at fat grafting, perioperative data, and preoperative and postoperative photographs were reviewed. Results: A total of 52 children underwent fat grafting as secondary revision for both unilateral and bilateral cleft lip repair. Fat was hand suctioned from the abdominal or buttock region with a mean yield of 3.0 mL (range, 2.0–5.0 mL). An average total volume of 3.0 mL (range, 2.0–4.5 mL) of fat was injected via an intraoral incision into the philtrum, vermillion, and volume deficiencies in the vertical component of the lip for volume restoration. No complications were noted with fat harvest or with fat grafting. Mean follow-up was 48 months. Postoperative assessment revealed improved volume symmetry in all patients, and all patients or families were pleased with the results. Conclusions: Fat grafting via an intraoral incision is a minimally invasive, safe, and reliable secondary procedure to improve volume asymmetries after cleft lip repairs.